2008
DOI: 10.1097/rhu.0b013e31817a241a
|View full text |Cite
|
Sign up to set email alerts
|

Drug Allergies May Be More Frequent in Systemic Lupus Erythematosus Than in Rheumatoid Arthritis

Abstract: Drug allergies are more frequent in SLE than in RA. Sulfa drugs are still the most frequent cause of drug allergies in SLE. Allergies because of drugs forbidden in the United States but easily available in specific ethnic groups are frequent in patients with SLE and RA. Their specific consumption must be intentionally assessed in cases of suspected drug allergies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 13 publications
2
11
1
Order By: Relevance
“…The low number of AIDS patients in our hospital might explain these findings. Previous studies have shown that the risk of allergic reactions in SLE patients is higher than in rheumatoid arthritis patients and healthy controls [1,14]. However, SLE was not identified as risk factor for cutaneous ADR in the present study.…”
Section: Discussioncontrasting
confidence: 66%
“…The low number of AIDS patients in our hospital might explain these findings. Previous studies have shown that the risk of allergic reactions in SLE patients is higher than in rheumatoid arthritis patients and healthy controls [1,14]. However, SLE was not identified as risk factor for cutaneous ADR in the present study.…”
Section: Discussioncontrasting
confidence: 66%
“…The drug hypersensitivity reactions in patients might be manifested by many cofactors, such as individual medical history, coadministered drugs, underlying diseases, viral infections, regulatory T-cell population/function, genetic polymorphisms of metabolic enzymes/immune-related genes, or autoimmune disorders. 39,40 Therefore the results presented in this study could not be extrapolated simply to the clinical situations of patients.…”
Section: Discussionmentioning
confidence: 97%
“…For example, subjects with a prior medical history of viral infection (eg, HIV and human herpesvirus) or autoimmune disorders (eg, systemic lupus erythematosus) have been noted to be more susceptible to drug hypersensitivity. 33,34 Because OXC is the prodrug of CBZ and they share structural similarity, the cross-reactivity between CBZ and OXC to T cells has been examined in patients, and it has been reported that 33% of the patients who had a CBZ-induced rash also had OXC hypersensitivity. 35 T cells isolated from patients with CBZ hypersensitivity showed cross-reactivity to OXC in vitro.…”
Section: Discussionmentioning
confidence: 99%